Complicaciones de la vía excretora en el trasplante renal. - Moreno Sierra, Jesús; Redondo González, E.; Gómez Vegas, Ángel; Blázquez Izquierdo, J. (Clínicas Urológicas de la Complutense, 1999)
Sin resumen